Treatment of AL amyloidosis in the era of novel immune and cellular therapies - Sarubbi, Caitlin; Abowali, Hesham; Varga, Cindy; Landau, Heather (Frontiers in Oncology, 2024)
Light chain (AL) amyloidosis is a plasma cell disorder distinguished from multiple myeloma (MM) by the degree of organ involvement due to tissue deposition of misfolded proteins. Treatments for AL amyloidosis have largely been borrowed from those developed for patients with MM. High dose chemotherapy followed by autologous stem cell transplant (ASCT) has historically been associated with the best outcomes. The recent incorporation of Daratumumab into up front therapy represents a significant advance and has changed the treatment paradigm calling into question the role of ASCT. The development of very active novel immune and cellular therapies, specifically B Cell Maturation Antigen (BCMA) directed therapies, has similarly been transformative for patients with MM and are now being studied in patients with AL amyloidosis. These include chimeric antigen receptor (CAR) T cells, bispecific antibodies and antibody drug conjugates. Although limited, preliminary data in patients with relapsed and refractory AL amyloidosis are showing promising results and it is expected that the treatment landscape for AL amyloidosis will continue to evolve. Particular attention to safety, potential for organ recovery and quality of life will be important when evaluating new treatments and/or treatment paradigms.